2018
DOI: 10.1177/0284185118786077
|View full text |Cite
|
Sign up to set email alerts
|

Clinical routine use of virtual monochromatic datasets based on spectral CT in patients with hypervascularized abdominal tumors - evaluation of effectiveness and efficiency

Abstract: Background Virtual monochromatic images (VMI) generated using spectral computed tomography (CT) are promising recently available tools to improve diagnostic performance in oncologic patients. Purpose To investigate if virtual monochromatic datasets are suitable for clinical routine use in patients with hypervascularized abdominal tumors. Material and Methods A total of 41 patients with hypervascularized hepatocellular carcinoma (HCC), renal cell carcinoma (RCC), or neuroendocrine tumors (NET) were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
(32 reference statements)
2
14
0
Order By: Relevance
“…Z eff reflected the atomic number of the compound material; the denser the compound, the higher the effective atomic number (37,38). In lung cancer, gastric cancer, and rectal cancer studies, Z eff has proved helpful in the preoperative identification of benign and malignant tumors (39)(40)(41). Our study found that Z eff (nonenhancement) and Z eff (arterial phase) was significantly higher in the malignant group than in the benign group.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Z eff reflected the atomic number of the compound material; the denser the compound, the higher the effective atomic number (37,38). In lung cancer, gastric cancer, and rectal cancer studies, Z eff has proved helpful in the preoperative identification of benign and malignant tumors (39)(40)(41). Our study found that Z eff (nonenhancement) and Z eff (arterial phase) was significantly higher in the malignant group than in the benign group.…”
Section: Discussionmentioning
confidence: 59%
“…Selecting the module as "monoenergetic plus ROI", the largest possible (round) ROI was placed on the thyroid nodule on the monoenergetic images (70 KeV) (26). Lastly, the dual-energy spectral curve was obtained from 40 Quantitative analysis of Z eff was carried out with Rho/ Z. Rho/Z was measured in the nonenhanced and arterial phases. The same ROI was applied for the Z eff measurement.…”
Section: Thyroid Nodule Analysismentioning
confidence: 99%
“…Clinical applications of DECT‐based VMIs include metal artifact reduction, beam‐hardening correction, contrast and noise optimization, and material differentiation . In addition, DECT‐based VMIs can be used to assess fatty liver and hypervascularized abdominal tumors . Despite promising results obtained in recent investigations, the noise levels of DECT‐based VMIs were high at low and high keVs …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, VMIs and IMs have shown some potential to improve the diagnostic performance of CT in the differentiation of several types Diagnostics 2021, 11, 1539 2 of 10 of tumors and pathologies and therapy monitoring in these patients [11][12][13][14]. However, it is not possible to efficiently assess all kinds of images, as reading is too complex and time-consuming for clinical routine [15]. A solution to overcome this limitation could be to characterize lesions based on their Hounsfield unit (HU) slope to be extracted from VMIs [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…A solution to overcome this limitation could be to characterize lesions based on their Hounsfield unit (HU) slope to be extracted from VMIs [ 13 , 16 ]. While low keV levels are favored for detection of hypervascular lesions in the literature [ 15 , 17 , 18 , 19 ], one must be aware that low keV levels increase image noise, which in turn affects sensitivity, especially for detection of small lesions. A solution could be a hybrid approach combining the high contrast of low-keV images and the acceptable noise levels of high-keV images.…”
Section: Introductionmentioning
confidence: 99%